KONFLIK BATIN PERAN UTAMA DALAM NASKAH DRAMA SAMPEK ENGTAY KARYA N. RIANTIARNO KAJIAN PSIKOLOGI SASTRA - Hanna Zalfa Mulyawati; Wika Soviana Devi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
This study aims to describe the inner conflict in the main role of Engtay, in the drama script Sampek Engtay by N. Riantiarno using Sigmund Freud's Theory. The method used is a qualitative descriptive research method. The data used in this study are dialogue sentences, monologues delivered by the main character in the drama, data collection techniques using library techniques and using corpus data tables. From the results of this study, there are several forms of inner conflict experienced by the main character, including pain, disappointment, confusion, anxiety, failure. These factors cause the main character's inner conflict with Raden Mas Darmaji as his father, Ray Retno as his mother and Sampek. There are three styles used by the main character in overcoming inner conflicts, namely the fox style, the mouse deer style, and the turtle style. Keywords: Main Character, Inner Conflict, Literary Psychology, Drama, Sampek Engtay